Feminist political ecology and the economics of care in search of economic alternatives - Bauhardt, Christine 1962-; Harcourt, Wendy 1959- (Routledge studies in ecological economics, 2019)
This book envisages a different form of our economies where care work and care-full relationships are central to social and cultural life. It sets out a feminist vision of a caring economy and asks what needs to change economically and ecologically in our conceptual approaches and our daily lives as we learn to care for each other and non-human others. Bringing together authors from 11 countries (also representing institutions from 8 countries), this edited collection sets out the challenges for gender aware economies based on an ethics of care for people and the environment in an original and engaging way. The book aims to break down the assumed inseparability of economic growth and social prosperity, and natural resource exploitation, while not romanticising social-material relations to nature. The authors explore diverse understandings of care through a range of analytical approaches, contexts and case studies and pays particular attention to the complicated nexus between re/productivity, nature, womanhood and care. It includes strong contributions on community economies, everyday practices of care, the politics of place and care of non-human others, as well as an engagement on concepts such as wealth, sustainability, food sovereignty, body politics, naturecultures and technoscience. Feminist Political Ecology and the Economics of Care is aimed at all those interested in what feminist theory and practice brings to today's major political economic and environmental debates around sustainability, alternatives to economic development and gender power relations